Medically administered antibiotics, dietary habits, fluoride intake and dental caries experience in the primary dentition - Mariri BP, Levy SM, Warren JJ, Bergus GR, Marshall TA, Broffitt B. (Blackwell Synergy)
Dental caries continues to be a major public health problem in the US and other nations, particularly among younger children. Unfortunately, understanding of factors contributing to caries in this age group is incomplete and further studies are necessary.